Training in professional social responsibility at university - Reig-Aleixandre, Natalia; García Ramos, José Manuel; de la Calle Maldonado, Carmen (Revista Complutense de Educación, 2022)
UN 2030 Agenda stress the importance of its involvement not only as an entity, but also through the training of university students as future socially responsible professionals. However, there are few initiatives aimed specifically at developing the social conscience of university students. The subject "Education for Social Responsibility", at a private university in Madrid, seeks to train professionals with a social conscience and committed to the common good. Twenty-five years after its implementation in several university degrees, the aim is to analyse its impact when the graduate is already in the performance of his or her profession. We analysed a key group (272 people) who completed the course and a quasi-control group (252 people) who did not, through an empirical ex post fact study. The aim is to determine whether there is a differential effect on the degree of social responsibility. In particular: in their values, in their social conscience, in their commitment to others and to the environment, and in the approach of the profession as a service. We develop an instrument for measuring Professional Social Responsibility and subsequently confirm its reliability and validity. The results show that there are significant differences in favor of professionals who studied the subject at the university (F(1,522) = 4.25; p = .040; η² = .008). They have greater global social responsibility, a better perception of values and a better approach to the profession as a service. It is hoped that similar initiatives will be taken at other universities in order to make a difference in the training of socially responsible professionals.